Evaluation of lime application and tillage for partly reclaimed brackishwater fishponds in acid sulfate soils - Bantala, Dammang S.
This study was conducted from August 2, 1982 to March 5, 1983 using twelve 300 m2 earthen ponds at the Brackishwater Aquaculture Center (BAC) of the University of the Philippines in the Visayas, Iloilo. The effects of tilling and liming alone or in combination were evaluated on the physical and chemical properties of soil and water, primary productivity and fish yields of partly reclaimed brackishwater fishponds in acid sulfate soil. The treatments included no tilling and no liming, Treatment II; tilling but no liming, treatment III; and tilling as well liming,treatment IV. There was a general increase (0.5 to 1.0 unit) in dry soil pH of all treatments.The increase in pH was associated with the decrease in the concentrations of potential acidity, aluminum and sulfate. The concentrations of active iron and manganese were low and stable throughout the study period. All soil parameters measured were not significant among treatments at 5% level of probability. The concentrations of alkalinity, sulfate and aluminum in water were regulated by pH. iron exhibited higher concentrations in control that the treated ponds, while phosphorus showed slightly lower concentrations in tilled ponds than the others. In general, the values of pH, alkalinity, aluminum, sulfate and phosphorus in water were not significantly different at 5% level of probability. The over-all mean of the weekly gross primary productivity measured by diel oxygen method showed identical values for all treatments, although the control treatment had slightly lower values.But the differences were not significant. The fish yield was highest in treatment III (312.6 kg/ha). This was closely followed by treatment IV, II (306.2 and 304.2 kg/ha, respectively) and treatment I (265.7 kg/ha). generally, tilling and liming alone or in combination was not of the sol or water properties, primary productivity or the fish yield significantly. However, tilling pf pond bottom had better effects over that of liming. This indicates that the applications of lime is not necessary to circumvent the problems of acid sulfate if the ponds had been earlier reclaimed by repeated tilling and flushing. This also indicates that for improving acid sulfate soils, removing the acidity and other toxic elements is a better method than neutralizing them by liming; because in liming, regardless of the quantities applied the toxic elements nevertheless remain in the soil.